PENGARUH PELATIHAN LARI INTERVAL DAN HOLLOW SPRINT TERHADAP KAPASITAS VITAL PARU - Dody Sutiawan, I Wayan (Universitas Pendidikan Ganesha, 2013)
This research aimed to determine the effect of interval training and hollow sprint run to lung vital capacity. This research was quasi-experimental with